Yesus Kristus sebagai Arketipe Gereja: Menuju Gereja yang Terbuka Terhadap LGBT - Ressa, Yosia Polando (Faculty of Theology Duta Wacana Christian University, 2025)
AbstractThis paper challenges the church’s exclusion of LGBT individuals, who have been deemed sinners and thus unworthy of participating in ecclesiastical communion. This stance highlights a lack of understanding within the church regarding LGBT people, stemming from an absence of meaningful dialogue or engagement. The paper seeks to explore LGBT issues through Carl Gustav Jung’s psychological concepts of archetypes and individuation. The findings suggest that Jesus Christ, embodying solidarity and compassion, serves as an archetype for a church that embraces LGBT individuals. Jesus’ interactions and acceptance of those considered “other” provide a foundation for the church to welcome the LGBT community into its fold. AbstrakMakalah ini menyoroti penolakan gereja terhadap LGBT karena mereka terlanjur dicap sebagai pendosa sehingga tidak layak masuk dalam persekutuan gerejawi. Ini menunjukkan adanya kesalah-pahaman gereja mengenai LGBT karena tidak terjadi perjumpaan dan dialog yang baik. Makalah ini mencoba memahami persoalan LGBT dari pendekatan psikologi Carl Gustav Jung tentang arketipe dan individuasi. Hasil penelitian menawarkan imajinasi Yesus Kristus, sosok yang solider dan penuh kasih, sebagai arketipe gereja yang menerima kaum LGBT. Perjumpaan dan penerimaan Yesus terhadap “yang lain” menjadi dasar bagi gereja untuk membuka diri bagi kehadiran komunitas LGBT di dalam kehidupan bergereja.